FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG DALAM PERSPEKTIF TEORI AGENSI DAN PECKING ORDER - Faisal Riza, 11.05.52.0027; Meita Oktaviani, Rachmawati (Students Journal of Accounting and Banking, 2015)
This study aimed to test empirically the influence of internal factors (managerial ownership, institusional ownership,Â firm size, and growth company) against corporate debt policy on manufacturing companies on the Stock Exchange. The samplein this study was obtained by using the method of purposive sampling. Based on the existing criteria then we got the 102 companies that the research samples in the study with 2011-2013. This research was conducted by using multiple linear regression analysis. The results showed that simultaneous variables Managerial Ownership, Institutional Ownership, company size and growth of the Company together have an influence on the debt policy in manufacturing companies on the Stock Exchange. Partially (individual) variables Managerial Ownership, Institutional Ownership and Firm size has no effect on the dependent variable. While the companys growth effect on the dependent variable, namely Debt Policy.Keywords: Debt Policy, Managerial Ownership, Institutional Ownership, Firm Size, Growth Companies Â